The Peru-Japan FTA and its impact on fishmeal trade: Progress or retrogress? - Villalobos Tapia, Diana Lucía; Salazar Rodriguez, Jose Sebastian; Zúñiga Abregú, Romi Rubí (LACCEI, 2025)
This article aims to analyze Peru's fishmeal exports to Japan following the implementation of the Free Trade Agreement (FTA) in 2012. A study was conducted covering the period from 2000 to 2023, adopting a quantitative approach, correlational scope, and non-experimental design, utilizing statistical methods such as the Student’s T-test and tools like SPSS to achieve more accurate results. The findings revealed that from 2000 to 2011, when there was no FTA in place, exports were significantly higher compared to the post-FTA period, with the lowest records observed in 2015. Similarly, a Student’s T-test was performed to compare the pre- and post-FTA periods to assess its influence. The results yielded a value lower than alpha, leading to the rejection of H0, confirming that the FTA does have an effect on the FOB value of fishmeal exports. However, this influence was negative, as the agreement introduced new requirements and permits that companies did not previously need to engage in trade. Additionally, other environmental and social factors impacted product commercialization, such as the El Niño phenomenon in 2016 and the COVID-19 pandemic in 2020.